Presence of mercury and methylmercury in Baltic Sea sediments, collected in ammunition dumpsites. (December 2020) - Siedlewicz, Grzegorz; Korejwo, Ewa; Szubska, Marta; Grabowski, Miłosz; Kwasigroch, Urszula; Bełdowski, Jacek
Abstract: Methylmercury (MeHg) is the most toxic and dangerous form of mercury occurring in the environment. MeHg is highly bioaccumulative in organisms and undergoes biomagnification via the food chain. In the Baltic Sea munition dumpsites, methylmercury can be formed from mercury fulminate contained in primary explosives, as environmental conditions there favour methylation. MeHg in analysed sediments ranged from 19 to 2362 pg g −1 d.w., the concentration of mercury (HgTOT ) ranged from 4 to 294 ng g −1 d.w., and the values of MeHg/Hg ratio ranged from 0.1 to 2.0%. The obtained results confirmed that munition dumpsites are a source of mercury. The concentration of MeHg is elevated in a wider area than immediately next to dumped munitions. Presented results suggest that physical processes responsible for sediment and near-bottom water movement are diffusing MeHg signal, making munition dumpsites rather a diffuse source of MeHg than a number of point sources associated with particular munitions. Highlights: Dumped ammunition is a source of mercury to marine bottom sediments. Presence of ammunition can limit methylmercury production. Methylmercury concentration in sediments was range from 19 pg g −1 up to over 2.4 ng g −1 The methylmercury/mercury ratio in sediments was from 0.1 to 2.0%. Measured concentrations were comparable to studies in years 2008–2019, but lower than reported in 1990s.